Designs for Networked Learning: Using Personal Learning Networks to Build Intercultural Competence - Duin, Ann Hill (Proceedings of the International Conference on Networked Learning, 2016)
Participants will explore the use of a Personal Learning Network (PLN) for building intercultural competence. A PLN is a collection of people, information resources, organizations, and other connections that a networked individual values because the connections support and contribute to learning interests. Throughout our exploration and development of PLNs, participants will identify how these might be used to make “visible” our culturally based assumptions about identity, knowledge creation, knowledge sharing, and the knowledge most worth having. Workshop emphasis will be on both pedagogy and research and stems from recent literature on connectivism and networked learning.